Establishing normal range of fetal renal artery RI and PI values in singleton pregnancies during 18-38 weeks of gestation - Nadeem, Beenish; Malik, Naushaba; Zahoor, Anam (Journal of Rawalpindi Medical College, 2023)
INTRODUCTION: Human kidney constitutes an integral organ during the period of embryogenesis. The use of regular ultrasound during antenatal follow ups not only assesses structural aspects of fetal body but can also evaluate functional integrity of developing organs to some extent. Unfortunately, fetal renal hemodynamics has been studied more in western population which have better socio-economic status as well as good antenatal care. Our study aims at establishing a normal reference range for fetal renal artery indices in healthy Pakistani pregnant population which has not been done before. METHODOLOGY: This is a nonprobability convenient study investigating 130 healthy pregnant women during 18-38weeks of gestation. Resistivity and pulsatility indices (RI and PI) of the fetal renal arteries were evaluated dividing the patients in four groups as per their gestational age. Normal reference ranges of RI and PI values were established. P values for RI and PI were also being calculated. RESULTS: Mean values of the RI and PI of the fetal renal arteries were calculated. P value for RI is 0.05 and PI is 0.69. Hence the values remain unaltered with advancing gestational age. CONCLUSIONS: These reference ranges demonstrate the minimal change of the fetal renal hemodynamics during healthy pregnancies pertinent to our reference population. These may be applicable in antenatal practice to identify deviations from these reference ranges and will be beneficial in further studies related to prediction of fetal renal function.